Modelling electromechanical properties of 2D materials and heterostructures - Georgoulea, Nina (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
Strain, both naturally occurring and deliberately engineered, can have a considerable effect on the structural, electronic, and transport properties of 2D and layered materials. Uniaxial or biaxial heterostrain (i.e. different strain applied to different layers) modifies the stacking arrangement of bilayer graphene (BLG) forming Moiré superlattices. This subsequently influences the electronic structure and the transport properties of the bilayer. We performed Density Functional Theory (DFT) calculations to investigate the interplay between heterostrain and the resulting stacking in BLG. We found that above a critical strain of 1%, it is energetically favorable for the free layer to be unstrained, indicating a transition between uniform AB stacking and nonuniform mixed stacking. This suggests that even small levels of strain can provide a platform to reversibly engineer stacking or der and Moiré features in BLGs, providing a viable alternative to twistronics to tune the stacking order of the system, and consequently its properties. The domain walls between the AB and BAstacked gapped BLG have garnered in tense interest, as they host topologically protected, valleypolarised transport channels. The introduction of a twist angle θ between the bilayers and the associated formation of a Moiré pattern has been the dominant method used to study these topological channels, but heterostrain can also give rise to similar stacking domains and interfaces. We theoreti cally investigated the electronic structure of a uniaxially heterostrained BLG. We discussed the formation and evolution of interface localized channels in the onedimensional Moiré pattern that emerges due to the different stacking registries between the two layers. We found that a uniform heterostrain is not sufficient to create onedimensional topological channels in biased BLG. Instead, using a simple model to account for the inplane atomic reconstruction driven by the changing stacking registry, we showed that the resulting expanded Bernalstacked domains and sharper interfaces are required for robust topological interfaces to emerge. These states are highly localized in the AAor SPstacked interface regions and exhibit differences in their layer and sublattice distribution depending on the interface stacking. We conclude that heterostrain can be used as a mechanism to tune the presence and distribution of topological channels in gapped BLG systems, complementary to the field of twistronics. We then investigated the effect of the Poisson contraction, which can occur with the application of uniaxial heterostrain for heterostrained BLG. In this initial investigation, we do not include the effect of atomic relaxation on the electronic and transport properties of the interface channels. The inclusion of Poisson contraction ν with the application of heterostrain leads to the formation of 2D Moiré superlattices, similar to the ones created in twisted BLG. For low energies, the states in the AAstacked regions are highly local ized, whereas the SPstacked regions host states that form a network throughout the lattice (topological channels). Moreover, the SPstacked interface channels occur over a range of energies (dispersive channels), but they do not have the expected pattern. We explained this, due to the fact that different strains are applied along x and y directions. The over all transmission has very low values due to the existence of the AB/BAstacked gapped domains in heterostrained BLG with the application of large interlayer bias, compared to no bias. Consequently, heterostrained untwisted BLG is an alternative way to tune the electronic and transport properties of BLG, compared to twisted BLG, overcoming limitations relevant to achieving precise twist angle θ. In future work, we will extend this study for lower and larger values of heterostrain to investigate how the localization of states is affected. Also, we could study how transmission is modified by changing the value of heterostrain for this system, as similar studies have been done for twisted BLG.
APPROVED